Impaired Quality of Life and Need for Palliative Care in a German Cohort of Advanced Parkinson’s Disease Patients - Klietz, Martin; Tulke, Amelie; Müschen, Lars H.; Paracka, Lejla; Schrader, Christoph; Dressler, Dirk W.; Wegner, Florian (Frontiers in Neurology, 2018)
Background Parkinson’s disease (PD) is the second most frequent neurodegenerative disease of the elderly. Patients suffer from various motor and non-motor symptoms leading to reduced health-related quality of life (HRQOL) and an increased mortality. Their loss of autonomy due to dementia, psychosis, depression, motor impairments, falls, and swallowing deficits defines a phase when palliative care interventions might help to sustain or even improve quality of life. Objective The aim of this study was to investigate the current status of palliative care implementation and quality of life in a local cohort of advanced PD patients in order to frame and improve future care. Methods 76 geriatric patients with advanced idiopathic PD meeting the inclusion criteria for palliative care interventions were clinically evaluated by neurological examination using Movement Disorders Society Unified Parkinson’s Disease Rating Scale, Barthel Index, Montreal Cognitive Assessment Test, and a structured interview concerning palliative care implementation. Results HRQOL is severely reduced in our cohort of geriatric advanced PD patients. We found motor deficits, impairment of activities of daily living, depression, and cognitive decline as most relevant factors determining decreased HRQOL. Only 2.6% of our patients reported present implementation of palliative care. By contrast, 72% of the patients indicated an unmet need for palliative care. Conclusion Quality of life is dramatically affected in advanced PD patients. However, we found palliative care to be implemented extremely rare in their treatment concept. Therefore, geriatric patients suffering from advanced PD should be enrolled for palliative care to provide adequate and holistic treatment which may improve or sustain their quality of life.